2019
DOI: 10.2174/1389203719666190527080832
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Potency, Efficiency and Drug-likeness: A Story of Intuition, Misinterpretation and Serendipity

Abstract: The concept of ligand potency is briefly discussed here as well as why this is still a challenge for its complete comprehension. In this context, we explain also the meaning of ligand efficiency (LE), which has been greeted with both enthusiasm and criticism among the drug design audience. A full understanding of LE requires the complex interpretation of the potency concept presenting the uncertainty similar to this of the Zeno paradox. In reality, the efficiency of LE is caused by the high degree of preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…By introduction of piperazine methylsulfonyl, 18b1 possessed acceptable water solubility (13.46 μg/mL at pH 7.0) and reasonable milogP (4.52) with an improved Fsp 3 content (0.27). Furthermore, ligand efficiency (LE) as an emerging index is used to evaluate the balance between biological activity and drug-likeness 46 , 47 . A promising lead compound is considered to have an LE value above 0.3 48 , 49 , so 18b1 displayed appropriate LE value (0.32) as with ETR (0.41).…”
Section: Resultsmentioning
confidence: 99%
“…By introduction of piperazine methylsulfonyl, 18b1 possessed acceptable water solubility (13.46 μg/mL at pH 7.0) and reasonable milogP (4.52) with an improved Fsp 3 content (0.27). Furthermore, ligand efficiency (LE) as an emerging index is used to evaluate the balance between biological activity and drug-likeness 46 , 47 . A promising lead compound is considered to have an LE value above 0.3 48 , 49 , so 18b1 displayed appropriate LE value (0.32) as with ETR (0.41).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the five compounds had tPSA values ranging from 74.08 to 111.45 Å 2 , suggesting their advantage for intestinal absorption (< 140 Å 2 ) and inability to pass through the blood-brain barrier (> 60 Å 2 ). Like the rule of five, ligand efficiency is also an important metric, used to balance the potency and drug-like properties in drug candidate discovery [37]. As described in Table 6, 10a-c possessed reasonable LE values, while 10e and 10g were slightly deviated.…”
Section: Fsp 3 Value Water Solubility Ligand Efficiency and Other Drug-like Propertiesmentioning
confidence: 99%